1994
DOI: 10.1017/s0266464x00000300
|View full text |Cite
|
Sign up to set email alerts
|

Pageantry and the Popular Front: Ideological Production in the 'Thirties

Abstract: The British working-class pageants of the nineteen-thirties were curiously cross-bred between, on the one hand, the resolutely bourgeois civic pageants which had become popular around the turn of the century and remained so still, and, on the other, the new Soviet style of mass-declamations with agit-prop intent. Often ignored even by left-wing theatre historians, these pageants drew on other influences varying from endemic communal forms of creation such as choirs and processions to the work of contemporary, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…49 The rise of public pageantry in Nazi Germany was mirrored by an increase in naval public theatre in Britain, but it should be underlined that this was not simply a right-wing phenomenon as the Popular Front staged its own pageants in Britain during the late 1930s. 50 There had been voices which spoke against holding the pageant at Greenwich but the plans for the event were widely supported in the national press. The Greenwich Night Pageant was understood as a naval alternative to the Royal Air Force's annual display at Hendon, and the Army's tattoo at Aldershot, which only served to highlight the pageant's celebration of Britain's Naval heritage.…”
Section: Patriotism and Pageantrymentioning
confidence: 99%
“…49 The rise of public pageantry in Nazi Germany was mirrored by an increase in naval public theatre in Britain, but it should be underlined that this was not simply a right-wing phenomenon as the Popular Front staged its own pageants in Britain during the late 1930s. 50 There had been voices which spoke against holding the pageant at Greenwich but the plans for the event were widely supported in the national press. The Greenwich Night Pageant was understood as a naval alternative to the Royal Air Force's annual display at Hendon, and the Army's tattoo at Aldershot, which only served to highlight the pageant's celebration of Britain's Naval heritage.…”
Section: Patriotism and Pageantrymentioning
confidence: 99%
“…McCarthy have shown, for example, that historical pageants were used by 'Popular Front' and internationalist organisations respectively to promote their political causes; 44 the format was broad and popular for much of the twentieth century.…”
Section: Mick Wallis and Helenmentioning
confidence: 99%
“…32 In any case, the pageant form itself could be adapted for different uses: Mick Wallis, in an examination of interwar Popular Front pageantry, has shown that the pageant form could be adapted by a range of political organisations, to serve different political purposes. 33 Another example was a Communist Manifesto centenary pageant in 1948. 34 Based mainly on a local study, this article examines the roles that historical pageants played in the lives of the communities that staged them.…”
Section: 'Splendid Display; Pompous Spectacle': Historical Pageants Imentioning
confidence: 99%